2020
DOI: 10.1038/s41598-020-73010-6
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of unconventional natural gas by methanogens co-existing with sulfate-reducing prokaryotes in deep shale wells in China

Abstract: Biogenic methane in shallow shale reservoirs has been proven to contribute to economic recovery of unconventional natural gas. However, whether the microbes inhabiting the deeper shale reservoirs at an average depth of 4.1 km and even co-occurring with sulfate-reducing prokaryote (SRP) have the potential to produce biomethane is still unclear. Stable isotopic technique with culture-dependent and independent approaches were employed to investigate the microbial and functional diversity related to methanogenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have shown that diverse microbial communities including methanogens coexist with sulfate-reducing microbes with corresponding functional capacities in Sichuan Basin shale gas wells and surface facilities (e.g., storage tanks), and have identified sulfate-reducing and iron bacteria in FPW from the Tarim Basin. 59,126,127 In comparison, sulfidogenic bacteria (e.g., Halanaerobium) and methanogens (e.g., Methanohalophilus) are commonly detected in FPW collected from wastewater storage impoundments 128 and separators in unconventional plays such as the Barnett, Marcellus, Utica, and Duvernay. 81,82,129−135 Studies in North America have examined the adverse effects of microbes that survive in FPW, including infrastructure corrosion and chemical degradation.…”
Section: Unconventional Hydrocarbon Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that diverse microbial communities including methanogens coexist with sulfate-reducing microbes with corresponding functional capacities in Sichuan Basin shale gas wells and surface facilities (e.g., storage tanks), and have identified sulfate-reducing and iron bacteria in FPW from the Tarim Basin. 59,126,127 In comparison, sulfidogenic bacteria (e.g., Halanaerobium) and methanogens (e.g., Methanohalophilus) are commonly detected in FPW collected from wastewater storage impoundments 128 and separators in unconventional plays such as the Barnett, Marcellus, Utica, and Duvernay. 81,82,129−135 Studies in North America have examined the adverse effects of microbes that survive in FPW, including infrastructure corrosion and chemical degradation.…”
Section: Unconventional Hydrocarbon Developmentmentioning
confidence: 99%
“…Analysis of FPW microbiology is critical to designing FPW storage, treatment, reuse, and recycling strategies and to understanding downhole biogeochemical processes. Previous studies have shown that diverse microbial communities including methanogens coexist with sulfate-reducing microbes with corresponding functional capacities in Sichuan Basin shale gas wells and surface facilities (e.g., storage tanks), and have identified sulfate-reducing and iron bacteria in FPW from the Tarim Basin. ,, In comparison, sulfidogenic bacteria (e.g., Halanaerobium) and methanogens (e.g., Methanohalophilus) are commonly detected in FPW collected from wastewater storage impoundments and separators in unconventional plays such as the Barnett, Marcellus, Utica, and Duvernay. ,, Studies in North America have examined the adverse effects of microbes that survive in FPW, including infrastructure corrosion and chemical degradation. ,, Dilution of the fracturing fluid by formation water and the degradation of biocides often limits the performance of biocides in restricting microbial activities. ,, Meanwhile, persistent microbes may use a wide range of organic polymers in fracturing fluids such as choline and ethoxylate and glycol surfactants to adapt to high salinity and build adaptative immunity to survive downhole. , In several studies, researchers have performed functional and culture-based metabolite analyses of the key North American shale bacterial genus Halanaerobium, further confirming its capacity for sulfide production, which may cause infrastructure corrosion. …”
Section: Fpw Managementmentioning
confidence: 99%
“…1a ). Some species of Shewanella are capable of thiosulfate reduction ( 45 ), and Shewanella were reported as the predominant taxa in production fluids from the Sichuan basin, China ( 46 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exception is the work of Zhang et al . [ 15 , 16 ] in the Sichuan Basin, China. Interestingly, these studies revealed a lack of organisms that were previously considered ubiquitous (and often dominant) in fractured shale environments, such as Halanaerobium species [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these studies revealed a lack of organisms that were previously considered ubiquitous (and often dominant) in fractured shale environments, such as Halanaerobium species [ 5 ]. Instead, members of the genus Shewanella were found to dominate [ 15 , 16 ] . Thus, characterizing unexplored fractured shales can aid identifying the processes underpinning the differential distribution of these industry-relevant taxa .…”
Section: Introductionmentioning
confidence: 99%